Cretaceous beetles (Insecta: Coleoptera) in amber: the palaeoecology of this most diverse group of insects. Issue 4 (23rd November 2019) - Peris, David; Rust, Jes
Abstract: Beetles, the most successful group of invertebrates on Earth, have a worldwide distribution and an outstanding fossil record. In addition, they are well known as inclusions in fossil resin. In historical studies of fossil material, specimens were often named and described without placing the taxa in an ecological context. However, the research philosophy for fossil beetles has changed over the past few years. In this article, we summarize the palaeoecological interpretations of fossil beetles from Cretaceous ambers, which includes species from 69 families, most of which were described during the last 3 years. By analysing current habits of those families, we argue that saproxylicity was the most common feeding strategy for these fossil beetles. More specifically, fungivorous species appear to dominate. In contrast, we find only anecdotal evidence for the presence of wood-boring groups, and it is thus necessary to identify alternative abiotic or biotic processes that are responsible for the copious resin production at this time. Finally, the recent description of some beetles as gymnosperm pollinators during the Cretaceous lends more weight to the importance of amber studies in addressing the role of beetles in the evolution of pollination strategies.